KONSERVATISME PENDIDIKAN ISLAM - Eko Sumadi (AT-TAJDID, 2018)
This paper begins the discussion by examining the genealogy of al-Ghazali's thinking, then discussing ideas about his education, to attract its relevance to the current practice of moral education. There are several important points that are the result of this discussion; First, that al-Ghazali's intellectual journey in the search of truth is a very dynamic intellectual dialectic, although in the end, he overrides the ability of reason in seeking the ultimate truth, he has really optimized the role of reason by placing it in a very special position. Second, for al-Ghazali that the estuary of all educational activities is to get closer to Allah. Thus, among the reasons that made al-Ghazali identified as a conservative goalkeeper. Third, however many criticisms of al-Ghazali's concept of education, many of his ideas are still relevant today, especially in matters of character building and moral education.